PSYCHOLOGY OF THE SERVICEMAN'S LIFE AFTER CAPTIVITY - Khmiliar, O.; Apalkov, V. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
Among all types of severe challenges, that servicemen have to face during war, captivity is experienced differently. By significantly undermining serviceman's health, narrowing his future prospects, injuring his psyche and leading to a severe mental, moral crisis, captivity dramatically changes the life of an individual. After supervising long-term reintegration and post-isolation support of people released from captivity, the author of the article reveals the peculiarities of readaptation and mental state of servicemen in the first four to five weeks, after being released from the captivity. It was found out, that the mere fact of a soldier's physical return to a peaceful environment does not signify his return to the usual way of living, which he had before the captivity. Particular attention is paid to the course of interpersonal conflict, undesired memories, which involuntarily activate the memory mechanisms of the former prisoners of war, subsequently generating and leading to re-traumatization. The article reveals the peculiarities of the family members' interaction with the personality of a former prisoner of war. In this context, it is highlighted how servicemen with different adaptive potential and individual-typological characteristics reintegrate into the society. The specifics of serviceman's behavior, whose actions in the mass media spotlight were outlined. For the first time, the interconnection between social intelligence and the three constitutional personality types of servicemen (endomorph, mesomorph and ectomorph) had been proven, which made it possible to determine the extent to which this relationship is the key to the effective adaptation to peaceful life of freed prisoners.
Keywords: prisoner of war, behavior, release from captivity, psyche of a prisoner of war, undesired memories, social intelligence, adaptation to freedom